Implementation of Productive Waqf as a Strategy Economic Empowerment of Muslims - Muhammad, Syafik; Aji, Imam Purnomo (Indonesian Academy of Social and Religious Research (IASRR), 2024)
The role of waqf is very important in participating in building and improving the economy, especially in building community welfare. From the Islamic perspective, productive waqf is the concept of managing waqf assets to obtain results so that they can provide benefits to the community on an ongoing basis. Thus, several questions arise related to this discussion, first, what are the legal and theological foundations of productive waqf? Second, what are the benefits and implementation of productive waqf for the community, and third, what are the challenges and solutions in implementing productive waqf for the community? This research method uses the literature method with data obtained from reference books and journals related to related discussions. The conclusion in this article is the result of a discussion of matters related to the title of the article.